Ritme aktivitas penerbangan harian Tetragonula laeviceps (Smith) (Hymenoptera: Apidae) di Bogor - Indah Putri Januar Yustia; Aunu Rauf; Nina Maryana (Jurnal Entomologi Indonesia, 2017)
Tetragonula laeviceps (Smith) is one of the most common species of stingless bees in Indonesia. However, only few publications available on the flight activity rhythms of the species. Research was conducted with the objectives to determine flight activity of T. laeviceps in relation to daily times and various weather elements. Three colonies of T. laeviceps were observed hourly for 5 minutes beginning at 06.00 a.m. until 06.00 p.m. Number of bees entering with pollen or resin, as well as exiting with waste were counted. Flight activity was significantly different (P < 0.001) among times of day. The preferential times (acrophases) of flight activities occurred at afternoon (11 a.m. to 12 a.m.). Number of entrance and exit flights positively correlated (moderate) with temperature and light intensity, while negatively correlated (moderate) with relative humidity.